A financial systemic stress index for Greece - Dimitrios Louzis; Angelos Vouldis (European Central Bank (ECB), 2013)
The paper develops a financial systemic stress index (FSSI) for Greece. We present a methodology for constructing and evaluating a systemic stress index which: i) adopts the suggestion of Hollo et al. (2012) [Hollo, Kremer, and Lo Duca (2012) “CISS – A Composite Indicator of Systemic Stress in the Financial System” ECB Working Paper 1426] to incorporate time-varying correlations between different market segments, and uses a multivariate GARCH approach which is able to capture abrupt changes in correlations; ii) utilizes both market and balance sheet data; and iii) evaluates the FSSI utilizing the results of a survey, conducted among financial experts, in order to construct a benchmark chronology of financial crises for Greece, which in turn is used to investigate whether changes in the FSSI are good indicators for financial crises. The results show that the FSSI is able to provide a precise periodization of crises.
Keywords: G01; G10; G20; E44; 330; financial crisis; multivariate GARCH; stress index; systemic stress